C677T Methylenetetrahydrofolate Reductase (MTHFR) Gene Polymorphism in Schizophrenia and Bipolar Disorder: An Association Study in Iranian Population - Arzaghi, Seyed Masoud (Tehran University of Medical Sciences, 2011)
OBJECTIVE: The methylenetetrahydrofolate reductase (MTHFR) gene polymorphism C677T is suspected to be a risk factor for psychiatric disorders, but it remains inconclusive whether the MTHFR polymorphism C677T is imputed to vulnerability to schizophrenia and bipolar disorder. METHOD: We prompted impetus to appraise this polymorphism in an Iranian population. Therefore, 90 patients with bipolar disorder type I (BID), 66 patients with schizophrenia diagnosed according to DSM-IV criteria, and 94 unrelated controls with no history of psychiatric disorders were recruited for this study. Genotype distribution and allelic frequencies of C677T polymorphism were investigated. RESULTS: We found no robust differences between patients with BID and schizophrenia with control participants either for allele frequencies or genotype distribution of MTHFR C677T polymorphism. However, a trend toward an increased risk for T allele was observed in the BID patients [with odds ratio (OR) of 1.28(CI 95%: 0.8-1.31), p>0.05]. CONCLUSION: However, the present and some previous studies failed to elucidate possible interaction between MTHFR C677T polymorphism and vulnerability to schizophrenia and bipolar disorder; still some associations have been revealed in performed meta-analyses that warrant further studies.